Sapphic crossings : cross-dressing women in eighteenth-century British literature - Klein, Ula Lukszo, 1982- (Peculiar bodies: stories and histories., 2021)
"This book considers the figure of the cross-dressing woman in eighteenth-century culture and her role in representing the possibility of lesbian and transgender embodiments"--